Керамічний комплекс давньоруського горизонту поселення Софіївська Борщагівка (за матеріалами розкопок 2008—2013 рр.) - Гунь, М.О. (Археологія і давня історія України, 2018)
Публікацію присвячено функціональному та
морфологічному аналізу керамічного комплексу
середньовічного горизонту, розміщеного у південно-західних передмістях Києва — багатошарового
селища Софіївська Борщагівка, що з 2008 р. систематично досліджується Північною експедицією Інституту археології НАН України. Багатий асортимент виявлених розкопками керамічних виробів та розвинуті технології їх виготовлення свідчать
про високий рівень розвитку матеріальної культури місцевого населення. The specificity of the vessels reveals various information,
first of all about the life of the ancient population.
Therefore the study of the ceramic assemblage of
the Kiev neighborhoods allows not only to draw parallels
between the peculiarities of the living model of the villagers and the inhabitants of the capital, but also to
understand more deeply the social processes that took place during the times of the Kievan state.
The pottery collection from the settlement of Sofiivska Borshchahivka represents a wide assortment of
wares from the 11th—13th centuries, which were used as a tare, for cooking, and for dining. The ceramics for
storage of supplies are represented a few fragments, which are probably due to various reasons: living conditions,
use of alternative containers, etc. Kitchen pots show not only the versatility of such vessels but also
the changes in its typological and morphological characteristics for a long time.
Inviting of ethnographic materials made it possible to reconstruct the specific of using of certain vessels in
everyday life, as well as to clarify the function of their individual morphological elements.
The study of the ceramic collections allowed to understand the organization of pottery crafts, certain features
of spiritual culture, traditions and innovations of the society, and at least investigated some aspects of
everyday life of the Kiev neighborhoods population of the 11th—13th centuries.